Strategic conflict: A systems based pedagogical simulation - Stepanovich, Paul; Mueller, James (International Journal of Social Science and Education, 2017)
The paper describes a pedagogical simulation that allows students to explore strategic goal conflict within the context of systems theory. Systems theory emphasizes, among other things, complexity, non-linear relationships, unintended consequences, time delays, and dynamics. Another important aspect of systems thinking is contextual thinking, where objects or relationships cannot be taken as standalone or absolute, but are critically dependent on system structure and the environment. And while strategic planning has long emphasized the importance of environment, it may be difficult for students to experience or appreciate its importance in the planning process. The simulation provides an experiential exercise for a strategy course. The paper provides a summary of systems thinking and strategic goal conflict, a description of the simulation, teaching notes, and experience with the exercise.
Keywords: dept.mgt; ⛔ No DOI found

AACSB accreditation and possible unintended consequences: A deming view. - Stepanovich, Paul L; Mueller, James; Benson, Dan (The Journal of Education for Business, 2014)
The AACSB accreditation process reflects basic quality principles, providing standards and a process for feedback for continuous improvement. However, implementation can lead to unintended negative consequences. The literature shows that while institutionalism and critical theory have been used as a theoretical base for evaluating accreditation, W. E. Deming's philosophy has not. This article fills that void by examining possible negative consequences in meeting faculty qualification requirements in institutions with a teaching mission. © 2014, Copyright Taylor & Francis Group, LLC.
Keywords: AACSB accreditation; Deming; dept.mgt; profound knowledge